Rapid beam shaping using a digital micromirror device - Kara, Ravin (My University, 2020)
The ability to structure light into di erent pro les has many important applications such as materials processing and optical communications. Modern methods of structuring light involve the use of liquid crystal spatial light modulators (LCSLMs), owing to their versatility and robustness in optics and photonics experimentation. However, they have some limitations as they are sensitive to polarisation states of light, have slow refresh rates and are expensive. Traditionally used in digital light processing technologies, digital micromirror devices (DMDs) have been used in many research aspects pertaining to optics and photonics. They are composed of arrays of micromirrors that have binary operational states determined by the angle of tilt of each mirror about an axis. These states make DMDs amplitude-only light modulating devices, insensitive to polarisation states, have faster refresh rates and signi cantly cheaper compared to traditional liquid crystal spatial light modulators. We employ DMDs to create di erent structures of monochromatic light, from arbitrary shapes to at-top beams and spatial modes of light. We test the DMD's refresh rate and demonstrate mode switching at a rate of 3.57 Hz. We show a high quality in the generated beams, with correlation factors of more than 90%, and as such demonstrate a modern alternative to structuring light.
A dissertation submitted in fulfilment of the requirements for the degree of Master of Science, Faculty of Science, University of the Witwatersrand, Johannesburg, 2020